Inheritance Laws in Indonesia - Irawaty Irawaty; Diyantari Diyantari (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2017)
Indonesia implements civil law system. There are three sub legal systems which are implemented until today. They are: positive/national law system, Islamic law system, and Adat law system. The majority of Indonesians are Islamic believers. The people claim that they are a religious nation. However, the implementation of the inheritance law in accordance with the Islamic law and the Adat law is sometimes different. One of the ethnic groups which has different regulation in heritance is Minangkabau. Minangkabau inheritance adat law has been a controversy. It is because while they claim that all Minangkabau people are Islam, they implement an inheritance law that is said as violating the Islamic inheritance law. In Islam, inheritance is passed down to children, both daughter(s) and son(s) with the composition son(s) inherits two parts compared to daugther(s). Many people mislead that the Minangkabau inheritance law passes down the inheritance to daughter(s) only. This paper discusses: 1) how are inheritance matter regulated in each of the aforementioned sub legal system? 2) how is inheritance matter regulated in Minangkabau ethnic group?